2020
DOI: 10.1039/d0qm00154f
|View full text |Cite
|
Sign up to set email alerts
|

AIEgen based polymorphs with solvent regulated crystal-to-crystal switch properties

Abstract: An AIEgen with tunable polymorphism-dependent emission and solvent regulated crystal-to-crystal switch properties is reported. Our study has provided insight into the relationship between molecular stacking and emission properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Recently, many co-crystallized materials have been employed for the tuning of solid-state properties recently, such as fluorescence, mechanical chemical behaviors, and electron transfer. It is a practical method for the modulation of RTP properties through choosing different long-lived phosphors in co-crystallized materials. Considering the similar structures, good crystallization, and different RTP properties, CzBzCl and CzBzBr are chosen for the construction of co-crystal to modulate RTP properties. A series of CzBzCl / CzBzBr co-crystals with different mass ratios were obtained.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Recently, many co-crystallized materials have been employed for the tuning of solid-state properties recently, such as fluorescence, mechanical chemical behaviors, and electron transfer. It is a practical method for the modulation of RTP properties through choosing different long-lived phosphors in co-crystallized materials. Considering the similar structures, good crystallization, and different RTP properties, CzBzCl and CzBzBr are chosen for the construction of co-crystal to modulate RTP properties. A series of CzBzCl / CzBzBr co-crystals with different mass ratios were obtained.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Luminogens with an AIE effect (AIEgens) are opposite to ACQ molecules, which exhibit strong emission in the solid state due to the restriction of intramolecular motion (RIM) . Besides, the inherent twisted structures of AIEgens endow them with a certain degree of mobility in the solid state, making them promising candidates for solid-state study and applications . Meanwhile, according to the RIM mechanism, the emission behavior of AIEgens depends on intramolecular motion.…”
Section: Introductionmentioning
confidence: 99%
“…25 Besides, the inherent twisted structures of AIEgens endow them with a certain degree of mobility in the solid state, making them promising candidates for solid-state study and applications. 26 Meanwhile, according to the RIM mechanism, the emission behavior of AIEgens depends on intramolecular motion. Thus, the molecular motion in the solid state can be in turn reflected by the fluorescence variation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a more efficient strategy to achieve controllable and inverted handedness, supramolecular co-assembly offers a convenient platform to precisely regulate the arrangement of programmable building blocks via noncovalent interactions (π–π stacking, hydrogen bonds, hydrophobic interactions, van der Waals interactions, and metal coordination). On account of the dynamic and reversible features of noncovalent interactions, the supramolecular chirality and CPL properties of artificial supramolecular co-assembly systems can be rationally modulated by various stimuli, such as light irradiation, chiral or achiral additives, stoichiometry, assembling rate, and metal ions. Liu’s group reported that the chirality of cinnamic acid derivatives could be inverted with morphology changed from superhelices to nanokebabs upon ultraviolet light irradiation . Feng’s group fabricated l-phenylalanine hydrogels with controlled supramolecular chirality by cooperating with metal ions .…”
Section: Introductionmentioning
confidence: 99%